TEACHING SPEAKING THROUH SMALL GROUP DISCUSSION METHOD AT THE TEN GRADE STUDENTS OF SMKN 2 KARAWANG - Sakila, Rika; Kunaepi, Ahmad Rois (PROJECT (Professional Journal of English Education), 2018)
The objective of the research entitled “Teaching Speaking Throuh Group Discussion” at ten Grade student of SMKN 2 KARAWANG  was to find out whether or not teaching speaking using small group discussion technique was effective to increase the student speaking ability. The research used was used quantitative method one group pretest – postest design. The population of this research was 30 of the ten Grade student of SMKN 2 KARAWANG in academic year 2017 – 2018 and the sample was entire population. The instruments of this research was speaking test. The data of this research was collected by giving pretest and post test of speaking to the students sample. The collected data were analyzed using SPSS 23 version. The study found that the test of normality consist the data of pretest is (0,116) and the data of postest is (0,076). In addition the value of sig (2-tailed) 0,000 because of the sig value (2-tailed) <0,005 it can be conclude that using small group discussion can improve student speaking skill. Keywords : Teaching, Speaking, Small Group Discussion